Aprendemos a indagar mediante andamiajes cognitivos - Sagastegui Bazan, Leoncio Gaspar (2021)
The development of competences in the area of Science and Technology are important because they are part of the graduation profile of Regular Basic Education; however, there is a perceived failure in learning and loss of interest of students in areas related to science. Our proposal seeks to contribute to overcome this deficiency through the use of cognitive scaffolds in the development of the "Inquire" competence in the area of Science and Technology in first grade students of secondary education. The implementation of such scaffolds is carried out within the didactic processes of the area and the analytical rubric is used for the evaluation of achievements. The theoretical support is based on the contributions of constructivism and the approach of inquiry and scientific and technological literacy of the Ministry of Education. The pedagogical support is based on the methodology for teaching science, the use of media and materials, the formative evaluation and other didactic elements used in our professional practice. It is concluded that the cognitive scaffolds together with the didactic processes strengthen the development of the Inquiry competence in the area of Science and Technology; suggestions are included and in annexes, the cognitive scaffolds used in a learning session developed and monitored with formative evaluation criteria.